2023
DOI: 10.1002/pc.27601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon fiber and thermoplastic resin on laminates under lightning and dielectric strength tests

Ernesto Saenz,
Marcos del Rio,
Pablo Venegas

Abstract: The incorporation of carbon fiber (CF) and thermoplastic resin in wind turbine rotor‐blade represents a challenge for lightning events because CF conducts electricity and the behavior of thermoplastic resins is not well known. A comparative study with laminates with epoxy or thermoplastic resins was performed, using lightning and dielectric strength tests. Lightning tests revealed that resins behaved similarly; the current preferentially flowed in fiber direction and in zones with high contact between fibers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The last question is related to the relevance of simulated lightning strike tests to composite structures. A lightning strike causes local damage to various types of composite structures, such as protected CFRP composites with expanded copper mesh, unprotected CFRP composites, composites with and without paint layers [24,29,30,[68][69][70][71][72][73][74], composites with vertically interleaved fibers [74], composites containing electrically conductive nanofillers [75][76][77][78] and single-walled CNT tuball paper [79], composites with conductive coatings [80,81], metal-tufted composites [82], thermoset and thermoplastic composites [50,83], sandwiched composites [84], stitched composites [85], scarf-repaired composites [2], composites with mechanical fasteners [27], and adhesively bonded composite [86], as well as full-scale composite structures, such as wind turbine blades [18,[87][88][89]. Although existing simulated lightning strike experimental studies for CFRP composites primarily focused on unprotected and protected composites and composites with mechanical fasteners, the other composite structures are also of significant importance.…”
Section: Laboratory Lightning Strike Testsmentioning
confidence: 99%
“…The last question is related to the relevance of simulated lightning strike tests to composite structures. A lightning strike causes local damage to various types of composite structures, such as protected CFRP composites with expanded copper mesh, unprotected CFRP composites, composites with and without paint layers [24,29,30,[68][69][70][71][72][73][74], composites with vertically interleaved fibers [74], composites containing electrically conductive nanofillers [75][76][77][78] and single-walled CNT tuball paper [79], composites with conductive coatings [80,81], metal-tufted composites [82], thermoset and thermoplastic composites [50,83], sandwiched composites [84], stitched composites [85], scarf-repaired composites [2], composites with mechanical fasteners [27], and adhesively bonded composite [86], as well as full-scale composite structures, such as wind turbine blades [18,[87][88][89]. Although existing simulated lightning strike experimental studies for CFRP composites primarily focused on unprotected and protected composites and composites with mechanical fasteners, the other composite structures are also of significant importance.…”
Section: Laboratory Lightning Strike Testsmentioning
confidence: 99%
“…Zhu et al 14 prepared a dual conductive network of nickel‐coated carbon fiber woven fabrics (NI‐CFWF) for lightning strike protection, which remained a residual compression strength of 92.65%, higher than that of non‐protected CFRP which is 87.89%. Saenz et al 15 conducted lightning strike tests on carbon fiber laminates with epoxy or thermoplastic resins Subsequent mechanical tests revealed that the lightning current did not affect the tensile properties, but rather influenced the bending properties. Liu et al 16 developed a nickel‐coated carbon fiber veil capable of retaining high electrical conductivity after delamination, thereby enhancing lightning protection effectiveness.…”
Section: Introductionmentioning
confidence: 99%